Modelo de decisão sobre os municípios prioritários para o controle da AIDS no Estado da Paraíba usando Lógica Fuzzy - Sousa, Ana Carla Alves de (2012)
The number of aids cases in the state of Paraíba grows since the first notification. It s important to recognize the pattern of geographic distribution of aids to have greater control, and thereby, reduce the spread morbidity and mortality from this disease. Thus, this study aims to identify the municipalities according to the degree of priority for aids control in Paraíba state by proposing a decision model based on fuzzy logic. Ecological study that uses the aids cases registered in the database of the Secretary of Health of the State of Paraíba in the period 2000 to 2010. There were the following analyzes: descriptive analysis, frequency measures of aids in Paraíba, spatial analysis, spatialtemporal analysis and fuzzy logic. Have been reported in the study period, 3.036 aids cases in the state of Paraíba. The age group most affected was between 20-34 years with 1.410 cases (46.44%), greater number of cases in males, with 1.988 cases (65,5%) and 2442 (80,4% ) of aids cases reported in Paraíba are alive. The counties with the highest values for Relative Risk are concentrated in the coastal region of the state. Spatial analysis verified the presence of spatial clusters throughout the study period and a higher concentration of conglomerates in the coastal region of the state. In spatiotemporal analysis, we identified 14 clusters, which are more concentrated on the coast and in the interior of the state. The decision model was based on fuzzy logic with 6 input variables, 4 output variables and 472 rules. The municipalities of Paraíba state were categorized by the type of decision, so that 14 (6,27%) were considered as priority; 10 (4,48%) with a tendency to priority; 4 (1,81%) with a tendency to non-priority, and 195 (87,44%) as non-priority. The decision model based on fuzzy logic was satisfactory, because it's reached the goal proposed by this study, identifying the municipalities of Paraíba state in accordance with the priority for the control of aids, helping public health managers in reducing and/or prevention of aids in Paraíba municipalities.